DISP-08. DISPARITY OF RADIATION TREATMENT AND CLINICAL OUTCOME AMONG ADULT MEDULLOBLASTOMA PATIENTS. (14th November 2022) - Yang, Kailin; Dinh, Mina; Nam, Kireem; Madishetty, Sanjana; Kilic, Sarah; Scott, Jacob; Chao, Samuel; Murphy, Erin; Suh, John
Abstract: OBJECTIVES: Medulloblastoma is the most common malignant pediatric brain neoplasm, but its pattern of care among adult patients has not been standardized. Disparity in socioeconomic factors influence treatment decision and prognosis in many cancers. This study aims to analyze the impact of insurance and socioeconomic status on the clinical outcome of adult patients with medulloblastoma in the United States. METHODS: Adult patients (age 18 or older) with medulloblastoma in the brain diagnosed from 2004 to 2016 were identified from the National Cancer Database (NCDB). OS was evaluated with the Kaplan-Meier and Cox proportional hazards methods. Logistic regression was performed to assess the effect on dichotomized dependent variable. RESULTS: A total of 1, 282 adult patients with medulloblastoma were identified. The mean age was 29 years (range 18-85). 30.9% of patients were uninsured or had Medicaid, 83.2% were white, 81.9% received radiation therapy, and 59.9% received chemotherapy. Using univariate analysis, insurance status, radiation, and chemotherapy were statistically associated with OS. Uninsured/Medicaid patients were associated with poorer OS (HR 1.36, 95% CI 1.08-1.71, p < 0.01) compared to those with private insurance. Treatment with radiation therapy (HR 0.43, 95% CI 0.34-0.55, p < 0.01) or chemotherapy (HR 0.51, 95% CI 0.41-0.62, p < 0.01) portended improved OS. After adjusting for age, sex, race, and Charlson-Deyo comorbidity score, statistically significant differences in OS were seen for patients with no insurance/Medicaid. Using multivariate logistic regression, patients with either no insurance or Medicaid were less likely to receive radiation therapy (OR 0.69, 95% CI 0.51-0.95, p = 0.02) compared to patients with private insurance. CONCLUSION: Using a large national cohort of adult medulloblastoma patients, this study demonstrated the statistically significant disparity of patient outcomes with insurance status. An effort to address healthcare disparity and increase access to cancer care may improve the clinical outcome for adult patients with medulloblastoma.